Full waveform inversion with combined misfit functions and application in land seismic data - Song, Jianyong; Yang, Zhifang; Cao, Hong; He, Weiguang; Pan, Wenyong; Li, Meng; Tian, Na (Frontiers in Earth Science, 2023)
Full waveform inversion reconstructs the subsurface structures by matching the synthetic waveform to the observed one. Inaccuracy of the source wavelets, thus can, easily leads to an inacurate model. Simultaneously updating source wavelets and model parameters is a conventionally used strategy. However, when the initial model is very far from the true one, cycle-skipping exists and estimating a reliable source wavelet is very difficult. We propose a combinatory inversion workflow based on seismic events. We apply a Gaussian time window around the first break, and gradually increase its width to include more seismic events. The influence of inaccurate source wavelets is alleviated by applying a Gaussian time window around the first break to evaluate the normalized cross correlation based objective function. There are inevitable small model artifacts caused by inter-event interactions when calculating cross correlations. As a result, we switch to the optimal transport function to clean the model and update the source wavelets, simultaneously. The combinatory strategy has been applied to models with different types of geological structures. Starting from a crude initial model, we have recovered a high-resolution and high-fidelity model and the source wavelets in two synthetic experiments.Finally, we apply our inversion strategy to a real land seismic dataset in Southeast China, and get higher resolution velocity model. By comparing an inversion velocity profile with the well log information as well as comparing the recorded data with the simulated data, we conclude that our inversion results for the field data are accurate and this new strategy is effective.